Tracking spatio-temporal LULC changes in key ecological network elements using fragmentation metrics and a custom raster-based approach: A multi-scale study from Poland - Marta Kubacka; Witold Piniarski; Patryk Żywica; Amy E. Frazier (Ecological Informatics)
Ecological networks (ENs), comprising core areas, ecological corridors, and buffer zones, are crucial for conserving biodiversity and providing ecosystem services in fragmented landscapes. However, spatio-temporal land use and land cover (LULC) changes within these elements remain poorly understood, hindering effective landscape management. This study examines LULC dynamics in the Wielkopolska region (Poland) over three periods (2008, 2014, 2020) using a raster-based method that enhances fragmentation assessment by incorporating fine-scale features, including linear structures often overlooked in conventional datasets. EN components were analyzed at four spatial scales (supra-local, regional, national, international) and across buffer zones (250–1000 m) using landscape metrics to quantify spatial and temporal dynamics. Ecological corridors, primarily farmland areas (77 %), face a high risk of fragmentation. Built-up areas are expanding along EN boundaries (14.6 % in 2008, increasing to 16 % in 2020, within 250 m of EN elements). Buffer zones experience rapid LULC shifts, revealing vulnerability to edge effects and land-use pressure. Structural metric analysis identified a parsimonious set of indicators that reliably detected fragmentation patterns. Division and effective mesh size (mesh) emerged as the most robust for multi-scale fragmentation assessment, with the mean shape index (shape_mn), largest patch index (lpi), and percentage of like adjacencies (pladj) providing complementary insights into patch complexity and connectivity trends. Larger-scale EN components (national and international corridors) show greater stability, whereas smaller-scale corridors (regional and supra-local) are more vulnerable to fragmentation. These findings provide clear guidance for scale-sensitive monitoring and planning strategies to improve EN resilience to land-use pressures, contributing to a comprehensive framework for assessing landscape fragmentation.